Implementation of Educational Values in PPKn Subjects in Primary Schools - Qori Difani (International Journal of Students Education, 2024)
This research was conducted with the aim of finding out and analyzing more deeply the implementation of Character Education in Civics Learning in Elementary Schools. As well as reviewing what efforts and to what extent have been made by teachers and elementary schools in Indonesia to implement character education, especially in Civics learning in elementary schools. This research uses the Literature Review method by searching for research results from several journals that are relevant to the problem being studied, such as from the indexers Google Scholar, Sinta, Basicedu, Hafeccs and so on. The results of this research show that a person’s character, which forms their personality, is formed through genetic and environmental influences. This character is reflected in daily attitudes and behavior, moral feelings and application in everyday life.